1992
DOI: 10.1016/0016-7037(92)90091-v
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine in silicate glasses: A multinuclear nuclear magnetic resonance study

Abstract: Abstract-Anhydrous nepheline, jadeite, and albite glasses doped with F as well as hydrous F-containing haplogranitic glasses were investigated using "F combined rotation and multiple-pulse spectroscopy; 19F + 29Si cross-polarization/magic angle spinning (MAS); and high-power r9F decoupled 29Si, 23Na, and 27A1 MAS nuclear magnetic resonance methods. Fluorine preferentially coordinates with Al to form octahedral AIF:-complexes in all glasses studied. In addition, F anions bridging two Al cations, units containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
93
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 25 publications
16
93
0
4
Order By: Relevance
“…Gaetani et al 2003). Previous work on F and Cl solution behavior in aluminosilicate melts (Mysen and Virgo 1985;Kohn et al 1991;Schaller et al 1992;Zeng and Stebbins 2000;Mysen et al 2004;Zimova and Webb 2006;Baasner et al 2013) have shown that F preferentially bonds with tetrahedrally coordinated cations such as Al and Si. Although in more complex melts such as basalt, F can also preferentially bond with Mg (Kiczenski et al 2004;Filiberto et al 2012) and form more complex bonds as Al-F-Ca or Al-F-Na (Zeng and Stebbins 2000;Mysen et al, 2004); Si-F and Al-F are always found.…”
Section: Effect Of Melt Structure On F and CL Partition Coefficientsmentioning
confidence: 95%
“…Gaetani et al 2003). Previous work on F and Cl solution behavior in aluminosilicate melts (Mysen and Virgo 1985;Kohn et al 1991;Schaller et al 1992;Zeng and Stebbins 2000;Mysen et al 2004;Zimova and Webb 2006;Baasner et al 2013) have shown that F preferentially bonds with tetrahedrally coordinated cations such as Al and Si. Although in more complex melts such as basalt, F can also preferentially bond with Mg (Kiczenski et al 2004;Filiberto et al 2012) and form more complex bonds as Al-F-Ca or Al-F-Na (Zeng and Stebbins 2000;Mysen et al, 2004); Si-F and Al-F are always found.…”
Section: Effect Of Melt Structure On F and CL Partition Coefficientsmentioning
confidence: 95%
“…F interacts strongly with silicate melts (Lange 1994) by breaking framework bonds and forming Al-F (Kohn et al 1991;Liu and Nekvasil 2001;Schaller et al 1992;Zeng and Stebbins 2000) and Si-F complexes (Liu and Nekvasil 2002;Zeng and Stebbins 2000) in the melt. F suppresses the solidus temperature below that of the halogen-free water-saturated solidus, thereby allowing the production of greater volumetric abundances of these silicic compositions.…”
Section: The Possible Effects Of Fluorinementioning
confidence: 97%
“…Moreover, the viscosity and liquidus of silicate melt decrease with increasing F contents in melt as a result of removal of more Al from bridging AlO 4 -units due to complexing with F, which caused depolymerization and lower liquidus of the melt. The presence of F in granitic melts will lead to the increase of the solubility of high field strength cations by making nonbridging oxygen atoms complex with these cations [54,55] . Fluorine is preferentially distributed in melt and the distribution coefficient of F is generally less than 1 between aqueous fluid and silicate melt at high pressure and temperature, so that F should be enriched in this kind of melts through granitic crystallization and differentiation [46,56,57] .…”
Section: Distribution Behaviors Of F and CLmentioning
confidence: 99%